Relasi Islam dan Politik Di Indonesia (Perdebatan Seputar Ideologi dan Konstitusi Negara Indonesia Merdeka) - Wahyuddin G (Jurnal Adabiyah: Humanities and Islamic Studies, 2016)
Islam and Politic have interrelationships. It consists of fungtional Islam and politics is a unity that can not be separated. Islam and politics have the correlation functional; Islam requires political support, while the political needs of moral and ethics of Islam. The relationship between Islam and politics can be viewed from two aspects. Firstly, there are several doctrines aspect, the phrase of the Qur'an which is often interpreted as a political concept referring to Islam. Second, the social reality. Having been Hijrah Year 622 H., the Prophet Muhammad Saw., has formed the Government of Madinah through a political contract with residents of the city of Madinah, consisting of Jewish, Islamic, and Arabian community who still adhere to the traditions and ignorance. The political contract is defined into a shahifah, and then it is known ‘Madinah Charter’. At the time, a small Committee was formed which compromises between the nasinalism and Islam to stem the various differences between the Islamic and the secular nationalists in BPUPKI who designed the Preamble and the Declaration of the independence day of Indonesia. This small Committee is managed to formulate the script 'Jakarta Charter'. In essence, the Charter affirms the Pancasila as the ground state with the addition of a sentence on the sila of the Godhead to be: believe in God with the obligation of running Islamic jurisprudence for the hangers. The next compromise occurred on August 18th 1945, changing the clause of the divinity with the obligation of running Islamic jurisprudence for the hangers which becomes "the divinity of the one true God".